1979
DOI: 10.1177/0193841x7900300409
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing From Single Case Studies

Abstract: Although studies of single cases occur throughout research fields, they are only recently beginning to appear in evaluation. These studies are difficult to generalize from, because statistical techniques do not apply. This article offers a variety of suggestions for logically analyzing the relationship between a single case and a population so that reasonable generalizations may be possible. Methodologies used by clinicians and by court justices are also examined for their relevance to evaluation methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
141
0
14

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(155 citation statements)
references
References 14 publications
0
141
0
14
Order By: Relevance
“…(This limitation is considered even more severe if the study involves a single case.) Often this is expressed as absence of external validity -the impossibility of extending the case study findings to a population of other cases (Donmoyer, 1990;Kennedy, 1979;Yin, 2009). Supporters of single case studies have developed a series of arguments -to be examined below -to solve the problem of "a sample of one" but none of the arguments has convinced those in favor of generalization by means of multiple cases or statistical samples.…”
Section: Criticism Of the Case Study As A Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(This limitation is considered even more severe if the study involves a single case.) Often this is expressed as absence of external validity -the impossibility of extending the case study findings to a population of other cases (Donmoyer, 1990;Kennedy, 1979;Yin, 2009). Supporters of single case studies have developed a series of arguments -to be examined below -to solve the problem of "a sample of one" but none of the arguments has convinced those in favor of generalization by means of multiple cases or statistical samples.…”
Section: Criticism Of the Case Study As A Research Methodsmentioning
confidence: 99%
“…Authors such as Donmoyer (1990), Kennedy (1979) and Yin (2009), believe increasing the number of data points in a single case would eliminate the problem. However, even with a larger number of data points, the single case remains unique (Ruddin, 2006).…”
Section: Criticism Of the Case Study As A Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kennedy [1979] proposed two approaches for cross-case analysis: a case-survey approach and a case comparison approach. Huberman and Miles [2002] indicated that cross-case analysis may carry the risk of achieving premature or false conclusions.…”
Section: Cross-case Analysismentioning
confidence: 99%
“…One way to the manage this is to analyse data from different perspectives. Kennedy [1979] proposed two conditions to conduct the comparison; first, isolated factors within particular case studies must be worthy of substantive attention; second, the number of case studies must be large enough to warrant cross-case tabulations. When these conditions are in place, cross-case comparisons can be made to establish cross-case patterns.…”
Section: Cross-case Analysismentioning
confidence: 99%